The Analysis of Students Mathematic Problem Solving Ability During Online Learning - M. Arif Wahyu Daroini; Tri Novita Irawati; Sholahudin Al Ayubi (Universitas Islam Jember, 2021)
This study aims to determine students' mathematical problem solving abilities based on their high, medium and low level of ability in solving the problem. This type of research is descriptive qualitative. The data collecting method that use are observation, test, and interview. The results showed that the problem-solving ability of high-level subjects reached an average of 75%, the problem-solving abilities of medium-level subjects reached an average of 67%, the problem-solving abilities of low-level subjects reached an average of 67%, out of a maximum score of 100. The result of interview, ability level high, medium, and low, students are capable and good even though it does not reach 100%. So, it can be concluded that high, medium, and low level abilities are good for going through the problem solving ability indicator. Keywords: problem solving, online learning